Permeance based algorithm for computation of flux linkage characteristics of non-linear 6/4 Switched Reluctance Motor (SRM) - Tamjis, Mohamad Rom; Mat Hanafiah, Mohd Ariff; Ahmad Aizan, Zulkefle; Ibrahim, Mazree; Syed Salim, Syed Najib; Ab. Ghani, Mohd Ruddin; Ab.Rahman, Puteri Nur Suhaila; S. N. M. Shahril; Ahmed, Dawood Saleem; Mohamed Khairuddin, Mohamed Syafiq Akmal; Baharudin, Zikri Abadi; Abdul Rahman, Ahmad Idil; et al. (Asian Research Publishing Network (ARPN), 2016)
The concept of permeance is used in the analysis of flux linkage of 6/4 SRM. The aim of this paper is to develop an efficient algorithm exploiting the nonlinear feature of the 6/4 SRM using the aforementioned concept of permeance. The first step is to generate the relevant equations related to permeances of the 6/4 SRM under study. The 6/4 SRM’s magnetization curve is then derived from the summation of mmf drops at various blocks representing the motor. The air gap permeances are derived at various angles and 3-D leakage effects are taken into account. These permeances are used for the mmf drop computation. The algorithm is capable of efficiently computing mmf drop at every block to consequently yield a complete accurate nonlinear flux linkage feature of the 6/4 switched reluctance motor. In this way, the capability of the SRM to produce the expected four times the specific output torque due to operation in high saturation region compared to an equivalent induction motor as special the attribute of the SRM is demonstrated.